Determinants of pain in patients with symptomatic knee osteoarthritis - Behzad Heidari; Karimollah Hajian-Tilaki; Mansour Babaei (Babol University of Medical Sciences, 2016)
Background: Several factors are associated with the development or exacerbation of pain in knee osteoarthritis (KOA). In this study, we reviewed this context based on relevant studies. Methods: Recent published studies which have addressed the relationship between pain and KOA were summarized. Results: Correlates of the clinical, demographic features, laboratory tests and abnormalities on radiographic as well as magnetic resonance imaging (MRI) with the knee pain have been discussed. The results indicated that many factors such as synovitis, synovial effusion, obesity, as well as structural lesions determined by MRI or radiographic examination, serum cytokines, inflammatory markers are determinants of pain in KOA. Conclusion: This context requires further investigations for identification of additional factors which initiate pain in asymptomatic KOA